Woman, women, all of us: Plural feminism - França , Cecília de Campos (Seven Editora, 2024)
This work aimed to bring the discussion about plural feminism to highlight the history and its developments over time, the different claims and how difficult it has been to promote transformations in societies. However, despite the difficulties, there have been many women in all times who have fought for rights. And finally, it brought some Brazilian women who continue to be tireless in this fight. There are many of us in this battle and our daily lives show how our strength is expressed.  DOI:https://doi.org/10.56238/sevened2024.010-015